Moral Values in a Movie Entitled Frozen by Jennifer Lee - Ch. Evy Tri Widyahening; Ericha Nataliana Nugraheni; MH Sri Rahayu (Jurnal Multidisiplin Madani, 2023)
The objective of this research was to analyze the character education values which were described by the characters in “Frozen” movie. This research is classified as a qualitative research type using a descriptive approach. The data from this study comes from “Frozen” movie and dialogue. Then, in collecting data the researcher used documentation by watching the movie and reading the script. In analyzing data, the researcher used interactive data analysis by Miles and Huberman. To find the research's validity, triangulation data and triangulation theory were used to check validation for the data. The result of this research has demonstrated that there are character education values that could be found in the movie entitled Frozen, such as self-control, hardworking, friendly & cheerful, social care, and responsibility that depicted by the characters of Elsa, Anna, Kristoff, and Olaf